Moral Elements in the Ethical Code of Buddhism - Romesh, Khangembam (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The article attempts to illuminate the ethical perspectives of Buddhism (dividing into four sections) by exploring the true nature of moral elements, which form the foundation of Buddhist philosophy. The ethical concerns of Buddhism give more emphasis on renunciation and a selfless attitude towards constructive and spiritual moral development. All its concerns are related with the problem of human suffering. Only human being’s sincere effort can remove human suffering and can attain to a life totally free from all miserable conditions. Human being is enough to become master of all. To understand our action and conduct in every phase of our life is the core element of Buddhist moral principles. Buddhism is a system found wholly characterized by the ethical principle seeking the meaning of life in life itself. It is mainly based on the ethical way of living and prescribes rigorous codes to promote the living of a virtuous life.